Upaya Meningkatkan Hasil Belajar Peserta Didik Dalam Pembelajaran Aktivitas Kebugaran Jasmani Melalui Permainan Tradisional Kelas VIII B SMP N 2 Surakarta - Bambang Wijanarko; Hari Mukti SW; Muhammad Dion; Rehan Budianto; Dwi Adiyana BK; Wahyu Sholichatun; Intan Sari Rachmawati (CV Edujavare Publishing, 2024)
This research aims first to identify student activities through the use of traditional games to improve fitness in class VIII B SMP N 2 Surakarta. The second objective is to evaluate the results of traditional games in an effort to improve the fitness of students in the same class. The method used in this research is Classroom Action Research (PTK) based on the Kemmis and McTaggart model, which consists of two cycles with stages of planning, implementation, observation and reflection. The research instrument used was a student fitness test using the Indonesian Physical Fitness Test (TKJI) for ages 12-16 years. The research results showed an increase in student learning completeness from cycle I to cycle II, with the percentage increasing from 31.25% to 84.375%. The use of traditional games has also been proven to provide positive results in increasing student fitness, which is reflected in the increase in student success rates from cycle to cycle. Thus, the conclusion can be drawn that the use of traditional games is effective in increasing students' fitness in learning PJOK, especially on the topic of physical fitness.